Les conditions préalables au développement des études du Canada - Robert, Benoît (Canadian Journal of Education/Revue canadienne de l'éducation, 1977)
The author of this article has been involved in education through the Canada Studies Foundation for over six years. Professor Robert begins with a description and definition of the Canada Studies Foundation, whose objectives and mode of operation are unique on the educational scene in Canada. The second — and most important — part of the article deals with the prerequisites for the development of Canadian studies: the mutual respect, tolerance, and feelings of equality which must animate teachers and students from all parts of the country. This is the task that the Canada Studies Foundation has been tackling for the last six years with very real — if not spectacular — success. The author sees similarities between the CSF objectives for Canada and those of UNESCO, in which Canada is playing such a visible role.